High-entropy alloys. A new concept for the design of innovative structural materials - Kamkina , L.V.; Proidak , Y.S.; Mianovska , Y.V.; Guba , R.M.; Bezshkurenko , O.G. (Theory and Practice of Metallurgy, 2026)
Modern technologies require state-of-the-art materials that meet their conditions, regardless of operating conditions. Alloys with high entropy can replace traditional materials, work under impacts, dynamic loads, elevated temperatures, etc. These alloys are used for the manufacture of tools, molds, dies, mold casting in parts that require high strength, resistance to oxidation and wear, can also be used in environments with high corrosion resistance parameters (plumbing, marine conditions), in aggressive conditions and in the chemical industry. High entropy alloys are quite easy to investigate and control, and can be obtained by the same methods as traditional alloys, such as: casting, rapid melt quenching, film sputtering, electrolysis, and mechanical alloying. Electroslag remelting (ESD) can greatly improve the purity, hardening structure, and transverse mechanical properties of steel. However, the increasing demands on the mechanical properties of steel are prompting metallurgists to make more efforts to eliminate defects in steel microstructures such as shrinkage and segregation. The combination of directional crystallization technology with electroslag melting technology effectively eliminates macrosegregation in the cast ingot through a shallow molten metal bath controlled by directional crystallization. Increasing the strength of alloys can be achieved either by alloying a solid solution (elements in the internodes) or by isolating the solidification phases or artificially introducing microparticles. Curing phases (carbides, nitrides, carbonitrides, intermetals) can be endogenous (formed from elements introduced into the melt in a liquid state or during its solidification and subsequent cooling) or exogenous (usually introduced into the melt just before crystallization begins, and there is also an increase in size and deterioration in the distribution of solidification phases.